2015
DOI: 10.1007/s10570-015-0707-y
|View full text |Cite
|
Sign up to set email alerts
|

Gelation and decrystallization of cellulose by TAAHs/DMSO treatment and the role of anions and cations

Abstract: Compact crystalline cellulose was structurally transformed into a loose regenerated form using treatment with tetraalkylammonium halides in dimethyl sulfoxide (TAAHs/DMSO) and gel formation using water. Swelling of cellulose was affected by the TAAHs content in DMSO and the anion and/or cation type. The cellulose swelling ratio of TAAHs/ DMSO was in the order of F -[ Cl -[ Br -& I -due to differences between hydrogen bond basicity (b) values of TAAHs/DMSO. The swelling ratio varied with the cation size of tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Köhler and Heinze reported that solutions containing tetra‐alkylammonium halides in DMSO (TAAHs/DMSO) are useful for dissolution of cellulose. At room temperature, cellulose is dissolved by TAAHs/DMSO, which improves the application of DMSO . Wu et al .…”
Section: Current Production Methodsmentioning
confidence: 99%
“…Köhler and Heinze reported that solutions containing tetra‐alkylammonium halides in DMSO (TAAHs/DMSO) are useful for dissolution of cellulose. At room temperature, cellulose is dissolved by TAAHs/DMSO, which improves the application of DMSO . Wu et al .…”
Section: Current Production Methodsmentioning
confidence: 99%